EBG antenna design - Ee, Lee Yee (2017)
This report focus on the applying EBG to reduce mutual coupling between patch elements. Dumbbell shaped structure is etched on ground plane in different arrangement to suppress surface wave between coupling element. Dumbbell structure shows better effect when placed between patches along E-plane where the coupling is more severe. Circular shaped is also applied in periodic manners to form band gap according to Bragg’s reflection condition and therefore reduce mutual coupling. Simulations are done using CST Microwave Studio and the S-parameter with and without EBG is compared and discussed.